The Positive Impact of Parental Autonomy Support, Academic Socialization, Parental Responses, and Psychological Control on Muslim Students' Motivation - Simbolon, Siti Eni Aisyah; Kusumaputri, Erika Setyanti; Hadji, Almira Amilbangsa (Universitas Muhammadiyah Yogyakarta, 2023)
Encouraging autonomy among students in the academic setting is a strategy to promote continued education. One way to foster academic autonomy is through supportive relationships between the school environment and parents. This study assesses how autonomy, control, academic socialization, and parental response to academic grades predict students' autonomous academic motivation in Sleman Regency. This quantitative research employs cluster random sampling, using the SPSS 23.00 application to select five madrasah samples from 10 State Tsanawiyah madrasahs in Sleman Regency. A Likert-scale questionnaire was administered to 569 students to collect data. Data analysis involved conducting multiple regression analyses after performing classic assumption tests, including normality tests, linearity tests, multicollinearity tests, heteroscedasticity tests, and testing hypotheses. The analysis results revealed that three out of the six relationships tested are significant, while the other three variables are not. Specifically, parental autonomy support, behavioral control, and response without punishment significantly correlated with students' autonomous academic motivation. On the other hand, psychological control's relationship with academic autonomous motivation, the relationship between students' academic socialization and academic autonomous motivation, and the relationship between punitive responses and academic autonomous motivation were found to be insignificant. The findings recommend that parents adopt parenting styles that address children's psychological needs, connected to their motivation for academic autonomy.